Efforts to Improve Activity and Learning Outcomes with Contextual Learning Models Through E-Module Development - Faiza Nisa Abida; Nefi Yulianti; Lingga Ardhyo Surachman; Muhammad Fatihul Huda; Nadya Putri El-Afina (PT. Pena Produktif Kreatif, 2024)
This action research aims to improve student activity and learning outcomes through the application of contextual learning models with the development of e-modules in Class XI IPS 2 SMAN 2 Blitar. Initial observations showed that the sociology learning process in the class was not optimal, marked by low student activity in discussions and unsatisfactory learning outcomes, both individually and in groups. This was due to the limited learning models and media used. This study involved 34 students (19 females and 15 males) and was carried out in three cycles. Each cycle consisted of several meetings: two meetings in the first cycle, two meetings in the second cycle, and three meetings in the third cycle. Data was collected through observation, student worksheets, and documentation. The results showed that in the first cycle, only a few students showed above-average activity and learning outcomes. In the second cycle, there was a significant increase in activity, where students were more active in discussions during presentations. However, the highest learning outcome only reached a score of 4450 through the Quizizz application test. In the third cycle, there was a drastic increase in learning outcomes with the highest score reaching 9000. This study concluded that applying the contextual learning model with the development of e-modules significantly increased the activeness and learning outcomes of students in Class XI IPS 2 SMAN 2 Blitar.